Democracy and Development in Africa: The Nigerian Experience - Omodia, S.M. (Mediterranean Journal of Social Sciences, 2013)
This paper discusses the hyphen and buckle between democracy and development in Africa with specific focus on theNigerian State. Its major focus is anchored on the positive transformation of the standard of living of the people. Thistransformational change in the lives of the Nigerian people was unfolded through the factorial analysis of the concepts: poverty,quality of governance cum political participation and national integration. The conception and argument of the researcher isthat democracy as a political mechanism for development has witnessed minimal or no qualitative transformation in the lives ofthe people as it pertain poverty reduction, political participation and national integration as a result of poor governance. Thus,the researcher recommends that if democracy is to positively impact on development especially in the Nigerian State, there isneed for the present democratic system to be restructured in such a way that the system is largely integrative of the peoplethrough their involvement in policy or programme initiation at the party level, communal and national level. Coupled with theabove is the need for vibrant political opposition that would provide functional alternatives to issues that borders on poverty,performance and national integration.